2008
DOI: 10.1038/cr.2008.70
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the PI3K/AKT pathway mediates FSH-stimulated VEGF expression in ovarian serous cystadenocarcinoma

Abstract: There is evidence to suggest that follicle-stimulating hormone (FSH) can facilitate the neovascularization of ovarian cancers by increasing vascular endothelial growth factor (VEGF) expression in cancer cells, although the underlying molecular mechanism of this process is not well known. Therefore, we investigated the effect of FSH on VEGF expression in the ovarian cancer cell lines SKOV-3 and ES-2. Treatment with FSH significantly increased VEGF expression in a dose-and time-dependent manner. In addition, FSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 40 publications
11
50
0
1
Order By: Relevance
“…In our previous study, we suggested a model of FSH-VEGF stimulation in ovarian cancer (Huang et al 2008). With the results obtained in the current study, we can supplement this model as shown in Feng Y unpublished data 2010).…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…In our previous study, we suggested a model of FSH-VEGF stimulation in ovarian cancer (Huang et al 2008). With the results obtained in the current study, we can supplement this model as shown in Feng Y unpublished data 2010).…”
Section: Discussionsupporting
confidence: 58%
“…The observations that FSH increases the risk of ovarian malignancy and that pregnancies or oral contraceptives protect the ovaries by suppressing FSH secretion led to numerous studies (Brekelmans 2003), including our previous study (Huang et al 2008) that examined the role of FSH in ovarian carcinogenesis. Collectively, these studies demonstrated that FSH stimulates the growth of normal and immortalized ovarian surface epithelium (OSE) and ovarian cancer cell lines in a dose-and time-dependent manner (Feng et al 1996, Zheng et al 2000, Ji et al 2004.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations